Apoptotic cell clearance deficiencies - Herrmann, Martin (Henry Stewart Talks, 2007)
Anti-inflammatory and immunosuppressive effects of apoptotic cells, Autoimmune disease and clearance of dying cells, Clearance deficiency of apoptotic cells, Germinal centre tingible body macrophage deficiency, Model for the generation of nuclear autoimmunity, Annexin V as adjuvans for irradiated tumor cells
Archived at 2021/02/25